2010
DOI: 10.4028/www.scientific.net/amr.156-157.413
|View full text |Cite
|
Sign up to set email alerts
|

Demerit-GWMA Control Chart for Demerit Statistics

Abstract: A classical Demerit control chart is used to monitor the process through which various types of defects in complex products, such as automobiles, computers, mobile phones, etc. are found in general. As a technique for rapidly detecting small shifts of the process mean in the control chart, the EWMA(exponentially weighted moving average) technique is very effective. This study suggested the Demerit-GWMA control chart, combining the GWMA(generally weighted moving average) technique, which shows better performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A demerit scheme is used to monitor a demerit system containing different types of defects in an inspection unit. For instance, defects are classified in terms of categories or classes, for example, “Very serious,” “Serious,” “Moderately serious,” and “Minor.” Kang et al 39 proposed the GWMA demerit scheme to monitor the mean demerit number per unit by classes. It is shown that, in many situations, the GWMA demerit scheme has a better OOC performance than the Shewhart and EWMA demerit schemes.…”
Section: Gwma Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…A demerit scheme is used to monitor a demerit system containing different types of defects in an inspection unit. For instance, defects are classified in terms of categories or classes, for example, “Very serious,” “Serious,” “Moderately serious,” and “Minor.” Kang et al 39 proposed the GWMA demerit scheme to monitor the mean demerit number per unit by classes. It is shown that, in many situations, the GWMA demerit scheme has a better OOC performance than the Shewhart and EWMA demerit schemes.…”
Section: Gwma Schemesmentioning
confidence: 99%
“…Kang and Baik 73 proposed the DGWMA demerit scheme and they showed that, in many situations, it has better performance in detecting small shifts in the mean demerit number per unit by classes than the GWMA, EWMA, and Shewhart schemes discussed in Kang et al 39 …”
Section: Dgwma Schemesmentioning
confidence: 99%
“…Dodge found that defects of the complex industrial products such as automobiles did not occur only in a type, and in order to address this problem, he suggested classifying them into four classes as follows depending on the extent to which they affect various types of defects. Because such a Demerit control chart uses 3σ Center line and Control limits, it not only requires the normality assumption on the statistics, but it also is not sensitive to small shifts of the process mean [2,3,7].…”
Section: Classical Demerit Control Chartmentioning
confidence: 99%
“…The Demerit-GWMA control chart was first suggested by H.W. Kang et al [7] in 2011. Demerit-GWMA statistics( i W ) are defined as in the following equation ( 6), in a similar manner to GWMA statistics ( i G ).…”
Section: Demerit-gwma(generally Weighted Moving Average) Control Chartmentioning
confidence: 99%
See 1 more Smart Citation